1992
DOI: 10.1002/j.1460-2075.1992.tb05605.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific expression of SRF-related genes in the early embryo of Xenopus laevis.

Abstract: We have isolated two members of the RSRF protein family, SL‐1 and SL‐2, in Xenopus laevis. Both proteins contain SRF‐type DNA binding domains and are related to the human protein, RSRFC4. SL‐1 constitutes a novel member of the RSRF family whilst SL‐2 is similar to human RSRFC4 throughout its length. SL‐1 protein recognizes the consensus DNA sequence CTA(A/T)4TAR in vitro and can bind to the same regulatory sites as other A/T‐rich sequence‐specific binding activities, such as the muscle‐specific regulatory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
0
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 58 publications
7
71
0
1
Order By: Relevance
“…The involvement of E-boxes in mediating MRF activity in Xenopus is suggested by their presence in muscle-specific promoters (Su and Woodland, 1993;Gaillard et al, 1998). As observed in other species, strong evidence supports the notion that MRFs could cooperate with both ubiquitous bHLH proteins like E12 and E47 (Rashbass et al, 1992) and MEF2 proteins (Chambers et al, 1992) in the activation of musclespecific gene expression in Xenopus. During myotome development, XMRF4 mRNA is detected only at stage 18 (Jennings, 1992), suggesting that it is not involved in either muscle determination or early muscle differentiation, because many muscle gene products are already present before it is detectably expressed in primary muscle cells (Table 1).…”
Section: Muscle Gene Expression From Primary To Secondary Myogenesissupporting
confidence: 67%
“…The involvement of E-boxes in mediating MRF activity in Xenopus is suggested by their presence in muscle-specific promoters (Su and Woodland, 1993;Gaillard et al, 1998). As observed in other species, strong evidence supports the notion that MRFs could cooperate with both ubiquitous bHLH proteins like E12 and E47 (Rashbass et al, 1992) and MEF2 proteins (Chambers et al, 1992) in the activation of musclespecific gene expression in Xenopus. During myotome development, XMRF4 mRNA is detected only at stage 18 (Jennings, 1992), suggesting that it is not involved in either muscle determination or early muscle differentiation, because many muscle gene products are already present before it is detectably expressed in primary muscle cells (Table 1).…”
Section: Muscle Gene Expression From Primary To Secondary Myogenesissupporting
confidence: 67%
“…The MEF-2C cDNA hybridized to a transcript of 6 kb that was detected at high levels in skeletal muscle and brain ( Fig. 2A), unlike other MEF-2 transcripts, which are widely expressed (10)(11)(12). A larger transcript was also detected at low levels in spleen and kidney.…”
Section: Methodsmentioning
confidence: 97%
“…Insight into the nature of the factors binding the MEF-2 site has recently been provided by the isolation of cDNAs encoding proteins that exhibit the DNA binding properties of MEF-2 (10)(11)(12). These proteins, originally termed RSRFs, for related to serum-response factor…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these observations, additional transcription factors necessary for koza activity may be localized to kozaexpressing tissues. Such cofactors could include additional members of the MADS domain family, such as the Mef2 proteins, which are expressed in developing muscle tissue (Chambers et al, 1992;Edmondson et al, 1994) or SRF, which has been shown to physically interact with Nkx3-1 (Carson et al, 2000).…”
Section: Discussion Koza and Cellular Proliferationmentioning
confidence: 99%